2020
DOI: 10.3354/ab00733
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of phytoene and astaxanthin and related genes expression in Haematococcus pluvialis under sodium acetate stress

Abstract: Phytoene and astaxanthin are 2 important carotenoids in the green alga Haematococcus pluvialis. Under environmental stress, the synthesis of phytoene in H. pluvialis increases significantly, and phytoene is converted to astaxanthin through enzymatic catalysis. This paper analyzes the relationship between astaxanthin and phytoene accumulation in carotenoid synthesis pathways under different concentrations of sodium acetate (NaAc) by high-performance liquid chromatography. The highest concentrations of phytoene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(34 reference statements)
1
4
0
2
Order By: Relevance
“…The downregulation of fatty acid biosynthesis-related genes, especially the unsaturated fatty acid biosynthesis genes, from Stage SAHS_1 to SAHS_48 demonstrated that exogenous SA played a role in providing a protection mechanism for H. pluvialis cells against the abiotic stress caused by high NaAC. These results were consistent with the astaxanthin, and fatty acid accumulation speculated to stimulate the self-protective metabolism as a defense against the high concentration sodium acetate stress (Cong et al, 2020).…”
Section: How Salicylic Acid and High Concentration Of Sodium Acetatesupporting
confidence: 86%
See 3 more Smart Citations
“…The downregulation of fatty acid biosynthesis-related genes, especially the unsaturated fatty acid biosynthesis genes, from Stage SAHS_1 to SAHS_48 demonstrated that exogenous SA played a role in providing a protection mechanism for H. pluvialis cells against the abiotic stress caused by high NaAC. These results were consistent with the astaxanthin, and fatty acid accumulation speculated to stimulate the self-protective metabolism as a defense against the high concentration sodium acetate stress (Cong et al, 2020).…”
Section: How Salicylic Acid and High Concentration Of Sodium Acetatesupporting
confidence: 86%
“…They also demonstrated in another study that the transcriptional expression levels of eight carotenoid genes in H. pluvialis were all downregulated in the first 12 h (except BKT and PDS genes), follow SA25 treatment, and were less than 2.5-fold in comparison with Control follow SA25 treatment in 2-day cultivation (except PDS gene) (Gao et al, 2012b). The phytoene and astaxanthin biosynthesis-related genes were studied at the transcript level under NaAC stress by Cong et al (2020), who reported that CrtW and CrtZ, the two key enzymes involved in astaxanthin biosynthesis, were continuously upregulated since the 1st day of induction, while expression levels of PSY, PDS, and LCYB genes were continuously upregulated ever since the 3rd day of induction. He et al (2018) conducted systemic transcriptome analysis about three variables, including light, acetate, and Fe 2+ , to explore the molecular mechanism of astaxanthin accumulation in the red-cell stage of H. pluvialis.…”
Section: How Salicylic Acid and High Concentration Of Sodium Acetatementioning
confidence: 94%
See 2 more Smart Citations
“…Although it is noteworthy that acetate at higher concentrations could be toxic to the cells and adversely affect their growth ( De Swaaf et al, 2003 ), in the presence of low concentrations of Ac, various microalgae can grow well. Various studies also reported the utilization of Ac to not only enhance the growth of green cells but also induce the encystment of H. lacustris ( Cifuentes et al, 2003 ; Cong et al, 2020 ). In the present study, microscopic observations showed that cells did not form cysts when 5 mM Ac was added into the medium in the initial days of cultivation for batch experiments.…”
Section: Resultsmentioning
confidence: 99%